Lymphoepithelioma-Like Carcinoma of the Lung: An Unusual Case and Literature Review - Yuan-Chun Huang; Ching Hsueh; Shang-Yun Ho; Chiung-Ying Liao (Case Reports in Pulmonology)
We described a case of lymphoepithelioma-like carcinoma (LELC) of the lung of a 65-year-old man with initial symptoms of intermittent chest pain and mild shortness of breath for 2 weeks. A right-lung mass was noted on chest computed tomography (CT) scan and was proved histopathologically as LELC of lung after video-assisted thorascopic lobectomy. He was successfully treated with lobectomy with postoperative adjuvant chemotherapy and is alive without signs of recurrence for 36 months after the diagnosis. It is important for clinicians, pathologists, and radiologists to understand the clinical, pathological, and radiological presentations of this neoplasm to avoid improper clinical decision making and misdiagnosis.